Inflammation-related microRNA expression level in the bovine milk is affected by mastitis - Lai, Yu-Chang; Fujikawa, Takuro; Maemura, Tadashi; Ando, Takaaki; Kitahara, Go; Endo, Yasuyuki; Yamato, Osamu; Koiwa, Masateru; Kubota, Chikara; Miura, Naoki (PloS one, 2017)
MicroRNA (miRNA) in tissue and liquid samples have been shown to be associated with many diseases including inflammation. We aimed to identify inflammation-related miRNA expression level in the bovine mastitis milk. Expression level of inflammation-related miRNA in milk from mastitis-affected and normal cows was analyzed using qPCR. We found that expression level of miR-21, miR-146a, miR-155, miR-222, and miR-383 was significantly upregulated in California mastitis test positive (CMT+) milk. We further analyzed these miRNA using a chip-based QuantStudio Digital PCR System. The digital PCR results correlated with those of qPCR, demonstrating upregulation of miR-21, miR-146a, miR-155, miR-222, and miR-383 in CMT+ milk. In conclusion, we identified miRNA that are upregulated in CMT+ milk. These miRNA exhibited sensitivity and specificity greater than 80% for differentiating between CMT+ milk and normal milk. Our findings suggest that inflammation-related miRNA expression level in the bovine milk was affected by mastitis, and miRNA in milk have potential for use as biomarkers of bovine mastitis.